Social impacts of the transformation of public space (City of Buenos Aires, 2007-2017) (2019)
This article proposes a reflection on the public policies of urban planning oriented to the reconfiguration of public space in the City of Buenos Aires since 2007 and its impact on the production and definition of new rules of use of that space. We understand that the restructuring of the public space from the implementation of the Sustainable Mobility Plan and the processes of urban regeneration of the Central Area of the City of Buenos Aires generates a new urban order where some uses of the city are configured as more legitimate than others. These policies affect the urban, on the spontaneity and dynamism of the public space and try to regulate it, discipline it and rationalize it. Besides there is an urban planning policy oriented to valorization of urban land that understands the city as a commodity. What type of city is being produced? For whom it is? What is the role of the State and private capitals in these processes? How and from what strategies a city is thought, planned and managed?